Does Vitamin D Deficiency Cause Hypertension? Current Evidence from Clinical Studies and Potential Mechanisms - M. Iftekhar Ullah; Gabriel I. Uwaifo; William C. Nicholas; Christian A. Koch (International Journal of Endocrinology)
Vitamin D deficiency is widely prevalent across all ages, races, geographical regions, and socioeconomic strata. In addition to its important role in skeletal development and calcium homeostasis, several recent studies suggest its association with diabetes, hypertension, cardiovascular disease, certain types of malignancy, and immunologic dysfunction. Here, we review the current evidence regarding an association between vitamin D deficiency and hypertension in clinical and epidemiological studies. We also look into plausible biological explanations for such an association with the renin-angiotensin-aldosterone system and insulin resistance playing potential roles. Taken together, it appears that more studies in more homogeneous study populations are needed before a firm conclusion can be reached as to whether vitamin D deficiency causes or aggravates hypertension and whether vitamin D supplementation is safe and exerts cardioprotective effects. The potential problems with bias and confounding factors present in previous epidemiological studies may be overcome or minimized by well designed randomized controlled trials in the future.